2007
DOI: 10.1093/schbul/sbl071
|View full text |Cite
|
Sign up to set email alerts
|

Psychiatric Symptoms and Quality of Life in Schizophrenia: A Meta-Analysis

Abstract: Quality of life (QoL) has been recognized as an important outcome of schizophrenia treatment, yet the determinants of QoL for individuals with schizophrenia are not well known. Research has consistently found psychiatric symptoms to be negatively related to QoL, however, findings concerning the strength of these relationships have been mixed, making it difficult to determine the degree to which such symptoms are related to poor QoL. This research presents a systematic meta-analysis of studies examining the rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

36
245
8
11

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 349 publications
(300 citation statements)
references
References 86 publications
(66 reference statements)
36
245
8
11
Order By: Relevance
“…The association between experiential deficits and SQOL appears to be significantly stronger than in previous studies which have examined the relationship to negative symptoms as a singular construct (Eack and Newhill, 2007;Narvaez et al, 2008;Priebe et al, 2011). In contrast to previous studies, the association between changes in experiential deficits and SQOL over time remained significant after controlling for depression (Priebe et al, 2011).…”
Section: Comparison With the Literaturecontrasting
confidence: 90%
See 2 more Smart Citations
“…The association between experiential deficits and SQOL appears to be significantly stronger than in previous studies which have examined the relationship to negative symptoms as a singular construct (Eack and Newhill, 2007;Narvaez et al, 2008;Priebe et al, 2011). In contrast to previous studies, the association between changes in experiential deficits and SQOL over time remained significant after controlling for depression (Priebe et al, 2011).…”
Section: Comparison With the Literaturecontrasting
confidence: 90%
“…While there evidence of a strong association between negative symptoms and objective quality of life (OQOL) (Ho et al, 1998;Hunter and Barry, 2012;Milev et al, 2005;Whitty et al, 2008), only a weak association between negative symptoms and subjective quality of life (SQOL) has previously been found (Eack and Newhill, 2007;Fitzgerald et al, 2001;Narvaez et al, 2008;Priebe et al, 2011). This may be because SQOL is determined by multiple processes, including the comparison between expectations and aspirations, a comparison with others, and adaptation over time, all of which may result in a less negative appraisal by individuals with chronic schizophrenia (Priebe, 2007).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The impact of psychopathology on QOL has been controversial and a recent meta-analysis (Eack and Newhill, 2007) reported that QOL was only modestly related to symptoms of mental illness.…”
Section: Qol and Psychopathologymentioning
confidence: 99%
“…Extensive reviews show that psychiatric symptoms, in particular, and psychopathology in general are important, albeit modest, contributors to the quality of life of people with schizophrenia, and that the influence exercised by them depends in part on the sample of study (11) . The mentioned authors emphasize the need to examine other psychosocial influences.…”
Section: Introductionmentioning
confidence: 99%